2014
DOI: 10.1021/sc4003505
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrothermal Pretreatment on Convective Drying Characteristics of Paper Sludge

Abstract: This work concerns the influence of hydrothermal (HT) pretreatment on sludge drying performance. Sludge was dried in an air duct dryer at a temperature of 30.4 ± 0.4 °C with a constant air velocity of 1.34 ± 0.04 m/s and a relative humidity of about 56%. Drying rate curves, defined as the mass flux (kg/(m2 h)) versus the dry basis moisture content (kg/kg), showed that the drying process mainly took place in the falling rate period. HT pretreatment can improve drying speed and shorten drying time. Six classical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 32 publications
2
25
0
Order By: Relevance
“…It is also visible that the thermal drying performance has also been improved by the HT. Zhao et al [179,180] investigated the dying performance of the HT pretreated and untreated paper sludge with an air duct dryer at an air temperature of 30.4±0.4 °C and velocity of 1.34±0.04 m/s. The results show that the drying process mainly took place in the falling rate period and was mainly controlled by the diffusion properties of the inner structure of the product.…”
Section: Dewatering and Upgradingmentioning
confidence: 99%
“…It is also visible that the thermal drying performance has also been improved by the HT. Zhao et al [179,180] investigated the dying performance of the HT pretreated and untreated paper sludge with an air duct dryer at an air temperature of 30.4±0.4 °C and velocity of 1.34±0.04 m/s. The results show that the drying process mainly took place in the falling rate period and was mainly controlled by the diffusion properties of the inner structure of the product.…”
Section: Dewatering and Upgradingmentioning
confidence: 99%
“…As HTC is ideally operated under saturated steam pressure, the energy required for evaporation can be avoided making the theoretical energy requirement for heating the reaction medium significantly lower compared to active drying [7,13]. Energy is still required for post-treatment separation of the solid and liquid phases, but can be significantly lower compared to conventional sludge drying due to potential sludge cell breakage and enhanced drying characteristics [14].…”
Section: Introductionmentioning
confidence: 99%
“…10 Moreover, the quality of emissions from combustion of SSderived hydrochars (SHCs) can be further improved. Parshetti et al 7 reported that emissions of CO and CH 4 were mitigated through cocombustion of SHC and low-rank coal. During the combustion of hydrothermally pretreated sludge, as a result of the transformation of protein structure via hydrothermal treatment, interactions between NO and NH 3 were facilitated, allowing NO emissions to be reduced.…”
Section: Introductionmentioning
confidence: 99%